The Role for Oxidative Stress in Aberrant DNA Methylation in Alzheimer’s Disease - L. Fleming, Jessica; J. Phiel, Christopher; Ewart Toland, Amanda (Current Alzheimer Research, 2012)
Alzheimer’s disease (AD) is a common, progressive neurodegenerative disorder without highly effective therapies. The etiology of AD is heterogeneous with amyloid-beta plaques, neurofibrillary tangles, oxidative stress, and aberrant DNA methylation all implicated in the disease pathogenesis. DNA methylation is a well-established process for regulating gene expression and has been found to regulate a growing number of important genes involved in AD development and progression. Additionally, aberrations in one-carbon metabolism are a common finding in AD patients with individuals exhibiting low S-adenosylmethionine and high homocysteine levels as well as low folate and vitamin B. Oxidative stress is considered one of the earliest events in AD pathogenesis and is thought to contribute largely to neuronal cell death. Emerging evidence suggests an interaction exists between oxidative stress and DNA methylation; however, the mechanism(s) remain unclear. This review summarizes known and potential genes implicated in AD that are regulated by DNA methylation and oxidative stress. We also highlight the evidence for the role of oxidative damage contributing to DNA hypomethylation in AD patients through several mechanisms as well as implications for disease understanding and therapeutic development.
Keywords: epigenetics